Study on performance and mechanism of enhanced low-concentration ammonia nitrogen removal from low-temperature wastewater by iron-loaded biological activated carbon filter. (1st January 2022) - Ren, Zhijun; Fu, Xiaolin; Zhang, Guangming; Li, Yuyou; Qin, Yu; Wang, Pengfei; Liu, Xiaoyang; Lv, Longyi
Abstract: In order to strengthen the treatment of low-concentration ammonia nitrogen wastewater at low temperature, iron-loaded activated carbon (Fe-AC) with ultrasonic impregnation method was used as the filter material of biofilter process. The performance and mechanism of ammonia nitrogen removal from simulated secondary wastewater by iron-loaded biological activated carbon filter (Fe-BACF) were studied at 10 °C. The characterization results showed that iron was loaded on the surface of AC in the form of Fe2 O3, and the specific surface area, total pore volume, pore size and alkaline functional group content of Fe-AC were obviously increased. After the formation of biofilm on the surface of filter media, the average removal rate of ammonia nitrogen by Fe-BACF (97.9%) was significantly higher than that of conventional BACF (87.8%). The improved surface properties increased the number and metabolic activity of microorganisms, and promoted the secretion of EPS on the surface of Fe-BAC. The results of high-throughput sequencing showed that the existence of Fe optimized the bacterial community structure on the surface of Fe-BAC, with the increase of the abundances of psychrophilic bacteria and ammonia nitrogen removal bacteria. The mechanism of enhanced ammonia nitrogen removal by Fe-BACF was the joint action of many factors, among which the main causal relationship was that modification of iron could optimize the number and category of microorganisms on Fe-BAC surface by improving the surface properties, thus improving the biological nitrogen removal ability. Results of this study provided a practical way for the treatment of low ammonia nitrogen wastewater in cold regions. Graphical abstract: Image 1 Highlights: Surface pore size and volume of iron-loaded activated carbon (Fe-AC) became larger. Fe-BAC filter showed better ammonia nitrogen removal capacity at low temperature. More biomass and stronger biological activity appeared on the surface of Fe-BAC. Modification of Fe promoted synthesis of more EPS on the surface of Fe-BAC. Bacterial community structure on the surface of AC was optimized by Fe modification.